Snakebite Incidence, General Awareness and Belief of Snakebite Management at a Rural Municipality of Eastern Nepal - Surya Bahadur Parajuli; Heera KC; Anish Luitel; Menuka Shrestha; Baidehi Upadhyaya (Journal of Nobel Medical College, 2022)
Background: Understanding people’s awareness on snakebite management would be highly beneficial to develop strategic program at local levels of Nepal. We aimed to identity snakebite incidence, general awareness and beliefs of people regarding snakebite management in rural communities.